Assessment of the existing and potential business models supporting agroecological transitions in Zimbabwe - Zingwena, Taurai; Matangi, Dorcas; Ngoma, Hambulo; Debello, Moti Jaleta; Chimonyo, Vimbayi G. P. (CGIAR, 2023)
Work Package Three (WP3) of the Agroecology Initiative (AE-I) aims to enhance the integration of agroecology principles in businesses as a way to facilitate the transition of agrifood systems towards agroecology. To achieve this, WP3 aims to collaborate with selected private sector companies to develop and implement business models (BMs) that support or are compatible with the agroecological transition further. This report outlines the re-engagement activities carried out by the AE-I team in Zimbabwe with the private enterprises between June and August 2023. The rationale was to engage with the private business entities identified in 2022, assess their interest in business models identified to have the best potential to support agroecology transition and propose to co-design new or existing business models that incorporate agroecological principles. Through consultative and participatory learning methods, three business entities (Hamara Chicks, PHI-Commodities, and PHI-livestock) are interested in partnering with the AE-I in Zimbabwe. The relevance of these business models from the perspectives of the 13 principles of Agroecology is also outlined. This activity is critical in improving intra-WP synergies, in particular linking output 3.3 on "Business model canvas development" to other succeeding activities and outputs.